2007
DOI: 10.1017/s0022112006004253
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer flow and bed shear stress under a solitary wave

Abstract: Liu & Orfila (J. Fluid Mech. vol. 520, 2004, p. 83) derived analytical solutions for viscous boundary layer flows under transient long waves. Their analytical solutions were obtained with the assumption that the nonlinear inertia force was negligible in the momentum equations. In this paper, using Liu & Orfila's solution and the solutions for the nonlinear boundary layer equations, we examine the boundary layer flow characteristics under a solitary wave. It is found that while the horizontal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
131
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(151 citation statements)
references
References 18 publications
18
131
2
Order By: Relevance
“…In the present work, the nonlinear boundary layer equations are solved. The result is compared to the linear boundary layer solution in Liu et al (2007) revealing that both profiles are disagreeing more than has been found before. A change of frame of reference has been used to allow for a classical linear stability analysis without the need to redefine the notion of stability for this otherwise unsteady flow.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…In the present work, the nonlinear boundary layer equations are solved. The result is compared to the linear boundary layer solution in Liu et al (2007) revealing that both profiles are disagreeing more than has been found before. A change of frame of reference has been used to allow for a classical linear stability analysis without the need to redefine the notion of stability for this otherwise unsteady flow.…”
mentioning
confidence: 76%
“…The third order approximate solution by Grimshaw (1971) for the potential Φ in 1 has been used by Liu et al (2007) and Blondeaux (2008, 2011) is thereby approximated by Grimshaw (1971): …”
Section: Inviscid Solitary Wave Solutionsmentioning
confidence: 99%
See 3 more Smart Citations